AN OVERVIEW OF ACADEMIC STRESS STUDENTS OF MEDICAL STUDENTS OF MATARAM UNIVERSITY FOR THE 2020 CLASS IN THE PANDEMIC ERA - Al Idrus, Fadhila Maulida; Mahardika, Agustine; Affarah, Wahyu Sulistya (Jurnal Ilmu Kesehatan, 2022)
The Covid-19 pandemic has hit various countries in the world, including Indonesia, which has had a considerable impact on various fields, including the field of education. The government imposed the Large-Scale Social Restriction or PSBB policy solely to reduce the spread of the corona virus so that all activities carried out outside the home must be stopped until the Covid-19 pandemic subsides. As a result, the teaching and learning process must be carried out online from their respective homes in order to minimize the spread of Covid-19. Therefore, first year medical students are more susceptible to stress than second and third year students. This study aims to describe the stress level of pre-clinical first-year medical students at the University of Mataram. This study used a cross-sectional (cross-sectional) research method, namely research conducted by observing for a moment or within a certain period and each study subject only made 1 observation during the study. The number of samples in this study amounted to 115 people. The research instrument used was the Medical Student Stressor Questionnaire. Then the results of research based on the MSSQ questionnaire have 6 domains with stressors that dominate the highest stress levels are academic stressors 62 people (53.91%). In the stress level domain, the most dominant is severe stress with the domain having the highest level of severe stress being the academic stressor domain and the one having the highest light stress being the intrapersonal and interpersonal stressor domain, but severe stress still dominates.